2014
DOI: 10.4172/2167-0846.1000162
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Chronic Low Back Pain in Adults: A Case Control Study Done in Sri Lanka

Abstract: IntroductionNot many risk factor studies for low back pain have been done in Sri Lanka. ObjectivesTo determine the association between low back pain and posture, exercise, family history, level of education, level of income, smoking, consumption of alcohol, body mass index (BMI) and consumption of animal proteins. MethodologyA case control study was done at two main teaching hospitals in Colombo North region Sri Lanka. This study was done on adult subjects. A pretested structured interviewer administered quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The results of the Quick Exposure Check Level (QEC Level) showed that as many as 17 respondents (42.5) needed further research and changes, 5 respondents (12.5%) were in safe conditions (Table 1). The results of the Quick Exposure Check Level (QEC) score calculation showed that most of the respondents (35%) with the exposure score for the back are at a high level, while for the shoulders (37.5%), wrists (50%) and neck 52%) is at a moderate level ( (Lionel, 2014). Musculoskeletal disorders occur with increasing age.…”
Section: Sample Characterizementioning
confidence: 99%
“…The results of the Quick Exposure Check Level (QEC Level) showed that as many as 17 respondents (42.5) needed further research and changes, 5 respondents (12.5%) were in safe conditions (Table 1). The results of the Quick Exposure Check Level (QEC) score calculation showed that most of the respondents (35%) with the exposure score for the back are at a high level, while for the shoulders (37.5%), wrists (50%) and neck 52%) is at a moderate level ( (Lionel, 2014). Musculoskeletal disorders occur with increasing age.…”
Section: Sample Characterizementioning
confidence: 99%
“…An extensive literature review of previous studies suggests that there is a strong association between high BMI levels and LBP which states that when compared with people with normal BMI, those with high BMI had a two times greater chance of developing LBP. 30 Others, however, discovered that the risk of getting LBP was not significantly correlated with either height or weight. 31 A recent study conducted on 300 patients revealed that out of 300 patients with LBP 74.6% were overweight or obese 32 which shows incongruity with our current study findings.…”
Section: Discussionmentioning
confidence: 99%
“…Low back pain is distress situated inferior to the 12th rib margin and superior to the lower gluteal folds, with the presence or absence of leg pain. Researches report that almost 18% of the population would develop LBP during their lifetime [4]. The most prevalent type of LBP is "non-specific LBP" because of non-identifiable clinical pathology.…”
mentioning
confidence: 99%
“…Researching the risk factors for LBP can help to minimize LBP and reduce the impact of acute LBP from transforming to chronic LBP. The leading risk factors of low back pain include age, sedentary lifestyle, anxiety, and sleep [4]. Besides various risk factors, I think the postural factor to be the greatest risk factor for LBP.…”
mentioning
confidence: 99%